2020
DOI: 10.1111/cod.13653
|View full text |Cite
|
Sign up to set email alerts
|

Patch test results of the European baseline series among 1309 patients in Turkey between 2013 and 2019

Abstract: Background: Prevalences of sensitivity to contact allergens change over time as a result of variations in allergen exposure. Objectives: The aim of the study was to describe trends in sensitisation to allergens of the European baseline series in Turkey between 2013 and 2019. Methods: The patch test results of 1309 patients with suspected allergic contact dermatitis (ACD) were analysed retrospectively, and the prevalence of contact allergies to European baseline series allergens was compared with previous data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 43 publications
(77 reference statements)
7
17
2
Order By: Relevance
“…A personal history of allergic disease was found in 57.3%, while a family history of atopy was noted in 58.7% of patients with a positive patch test. This is in contrast to a scientific study published in 2021, in which only 16% of participants reported a personal history of atopy (18). In another recent study, a history of hypersensitivity was found in one-third of participants (5).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…A personal history of allergic disease was found in 57.3%, while a family history of atopy was noted in 58.7% of patients with a positive patch test. This is in contrast to a scientific study published in 2021, in which only 16% of participants reported a personal history of atopy (18). In another recent study, a history of hypersensitivity was found in one-third of participants (5).…”
Section: Discussioncontrasting
confidence: 89%
“…In another study, the main anatomical site was also the hands, followed by the upper limbs at 64.8% and 44.6%, respectively (16). Similar results were also found in a Turkish study with hand involvement at 49.3% (18). The hands' predominance is due to daily activities, repeatedly exposing hands to various allergens.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The positivity rate of PPD in Japan is higher than that in Europe 15,16 . We found no significant sex difference in the positivity rate, and that the positivity rate of PPD increased with age (Table 3 and Figure 1).…”
Section: Discussionmentioning
confidence: 52%